The Binding Mode of Fusion Inhibitor T20 onto HIV-1 gp41 and Relevant T20-Resistant Mechanisms Explored by Computational Study - Qiu, Su; Yi, Hong; Hu, Jun; Cao, Zhijian; Wu, Yingliang; Li, Wenxin (Current HIV Research, 2012)
Enfuvirtide (T20), the first FDA approved fusion inhibitor for HIV-1/AIDS, displayed outstanding effects of fusion inhibition by binding to the envelope glycoprotein gp41. But with the continuous emergence of T20-resistant mutations, the exploration of T20's binding mechanism onto gp41 wild type (WT) and the related resistance mechanism is needed. In this work, a complete structure model of gp41 including the fusion peptide (FP) and HR1 in complex with three molecules of T20 was obtained by structural modeling and molecular dynamics simulation (MDS). In this T20-gp41 model, the T20 hydrophobic C-terminal composed of the eight-residue sequence “WASLWNWF” formed unstructured coil instead of a helical structure, which enabled more residues of T20 to contact gp41 to exert its antiviral activity. Essential residues Trp155, Trp159, Trp161 and Phe162 of T20 formed strong vdW interactions with some hydrophobic cavities on the gp41, as never seen in other gp41 trimetric core structures. Based on the T20-gp41 model, seven corresponding structure models of T20-resistant mutants G36D, I37K, V38E, Q39H, Q41R, N43D and L45M were constructed and fully equilibrated by MDS. Most remarkably, the I37K and Q41R mutations led to collapse of the coiled coil structure, causing greatest change in binding energy. Also notably, the V38E and N43D mutations hindered the binding of T20 through electrostatic repulsion and thus also resulted in dramatic change in binding energy. Besides, mutations G36D, Q39H and L45M only caused minor conformational and energetic changes. In all, these results could provide new clues for the design of T20-like peptide inhibitors to target the T20-resistant virus.
Keywords: G36D